Ezetimibe blocks the internalization of NPC1L1 and cholesterol in mouse small intestine - Xie 谢畅, Chang (The American Society for Biochemistry and Molecular Biology, 2012)
The multiple transmembrane protein Niemann-Pick C1 like1 (NPC1L1) is essential for intestinal cholesterol absorption. Ezetimibe binds to NPC1L1 and is a clinically used cholesterol absorption inhibitor. Recent studies in cultured cells have shown that NPC1L1 mediates cholesterol uptake through vesicular endocytosis that can be blocked by ezetimibe. However, how NPC1L1 and ezetimibe work in the small intestine is unknown. In this study, we found that NPC1L1 distributed in enterocytes of villi and transit-amplifying cells of crypts. Acyl-CoA cholesterol acyltransferase 2 (ACAT2), another important protein for cholesterol absorption by providing cholesteryl esters to chylomicrons, was mainly presented in the apical cytoplasm of enterocytes. NPC1L1 and ACAT2 were highly expressed in jejunum and ileum. ACAT1 presented in the Paneth cells of crypts and mesenchymal cells of villi. In the absence of cholesterol, NPC1L1 was localized on the brush border of enterocytes. Dietary cholesterol induced the internalization of NPC1L1 to the subapical layer beneath the brush border and became partially colocalized with the endosome marker Rab11. Ezetimibe blocked the internalization of NPC1L1 and cholesterol and caused their retention in the plasma membrane. This study demonstrates that NPC1L1 mediates cholesterol entering enterocytes through vesicular endocytosis and that ezetimibe blocks this step in vivo.